Perinatal outcome and clinical features of monochorionic monoamniotic twin gestation. Issue 5 (20th March 2013) - Murata, Masaharu; Ishii, Keisuke; Kamitomo, Masato; Murakoshi, Takeshi; Takahashi, Yuichiro; Sekino, Madoka; Kiyoshi, Kenji; Sago, Haruhiko; Yamamoto, Ryo; Kawaguchi, Haruna; Mitsuda, Nobuaki
Abstract Aim To clarify perinatal outcomes of monoamniotic (MM) twin pregnancies. Material and Methods MM twins delivered in seven tertiary perinatal centers during the last decade were retrospectively evaluated. All pregnant women were scheduled to begin inpatient management at around 24 weeks of gestation and undergo a planned cesarean section beyond 32 weeks. Pregnancy outcomes, prevalence of fetal death and cord entanglement, perinatal mortality and neuromorbidity rate at discharge were examined. Results The study group comprised 38 MM twin pregnancies (76 fetuses). Cord entanglement was confirmed in 88% (30/34) of women, and fetal deaths occurred in nine women (eight were both fetal deaths, and one was single fetal death). The cord entanglement accounted for 65% (11/17) of the fetal deaths. The median gestational age at delivery was 31+3 weeks, but that for viable infants was 32+3 weeks; the median birth weight was 1642 g, the perinatal mortality rate was 2% (1/60), and the neuromorbidity rate was 8% (5/50). The overall survival rate was 75% (57/76). Conclusion Perinatal outcomes in our study were relatively good irrespective of high frequency of cord entanglement. Close fetal monitoring may allow MM twin pregnancies to extend gestational age, which may contribute to reduce both fetal death and neonatal morbidity by immaturity, although the best delivery weeks remained undetermined.